2022
DOI: 10.1038/s41598-022-18741-4
|View full text |Cite
|
Sign up to set email alerts
|

X-ray attenuation of bone, soft and adipose tissue in CT from 70 to 140 kV and comparison with 3D printable additive manufacturing materials

Abstract: Additive manufacturing and 3D printing are widely used in medical imaging to produce phantoms for image quality optimization, imaging protocol definition, comparison of image quality between different imaging systems, dosimetry, and quality control. Anthropomorphic phantoms mimic tissues and contrasts in real patients with regard to X-ray attenuation, as well as dependence on X-ray spectra. If used with different X-ray energies, or to optimize the spectrum for a certain procedure, the energy dependence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…[12,55,56] The 20% GelMA solution was used specifically for the Au and AuMA NP ink groups, where the 12% GelMA concentration was not sufficient to maintain adequate printability and crosslinking of constructs. The concentration of each contrast agent in GelMA was selected as the lowest value that would generate clinically relevant X-ray attenuation (200-300 HU [57] ). The 20% GelMA solution and LAP photoinitiator was used specifically for the Au and AuMA NP ink groups, following previously established methods to optimize the photocrosslinking of constructs containing sufficient Au concentrations for X-ray contrast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12,55,56] The 20% GelMA solution was used specifically for the Au and AuMA NP ink groups, where the 12% GelMA concentration was not sufficient to maintain adequate printability and crosslinking of constructs. The concentration of each contrast agent in GelMA was selected as the lowest value that would generate clinically relevant X-ray attenuation (200-300 HU [57] ). The 20% GelMA solution and LAP photoinitiator was used specifically for the Au and AuMA NP ink groups, following previously established methods to optimize the photocrosslinking of constructs containing sufficient Au concentrations for X-ray contrast.…”
Section: Resultsmentioning
confidence: 99%
“…Standard (calibration) curves were first generated for the molecular (Gd chelate and Iod, Figure 3A) and NP (Figure 3F) contrast agents. According to the obtained standard curves, the lowest concentration of contrast agent to achieve an X‐ray attenuation readily detected with preclinical scanners (200–300 HU [ 57 ] ) was chosen to investigate retention. Longitudinal studies for the molecular contrast agents demonstrated a quick (burst) release of reagents within a 1‐h (Gd) or 2‐h (Iod) window in static and dynamic (rocking) conditions (Figure 3B–I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing popularity and accessibility of 3D printing technology, a variety of printing filaments are now available for printing human bone and soft tissue. Several studies have discussed materials for 3D-printed phantoms in CT [24]- [26]. Novel filament materials composed of hydroxyapatite and biocompatible, biodegradable polymers, such as CT-Bone (Xilloc Medical Int., Sittard-Geleen, the Netherlands), can be utilized for printing synthetic bone implants that rapidly induce bone regeneration and growth [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, materials such as vinyl and PLA with stone (PLA/stone) can offer up to nearly 1000 HU at 96.9% infill ratio at tube voltage of 120 kVp, as they exhibit relatively higher X-ray absorption. Additionally, considering materials for spectral CT phantoms, high impact polystyrene (HIPS) based filaments may be suitable for mimicking CT numbers in applications where energy dependence is important [26], because they show similar spectral profiles as the human body. In this study, we employed StoneFil filament, one type of PLA/stone filament.…”
Section: Discussionmentioning
confidence: 99%